Estudio de dispositivos de interconexión entre sistemas locales de generación de energía fotovoltaica y red de suministro nacional (2021)
In this degree work, the proposal of the study of interconnection devices between local photovoltaic power generation systems and the national supply network is presented, since currently at the national level and specifically in the city of Cúcuta Norte de Santander they are being implemented installations, applying the latest trends in photovoltaic solar energy and in most cases systems are implemented with the aim of meeting internal needs and redirecting excess energy to the public grid. This requires that these designs be carried out by qualified personnel who know how to apply the CREG 030 standard and the RETIE application with the regulations specified for this type of installation.